Menakar Transformasi Bawaslu Menjadi Lembaga Independen Peradilan Pemilukada - Aprilian Sumodiningrat (Jurnal Konstitusi, 2022)
Since Law Number 12 of 2008, there has been a change in the regulation of the institution's power that settles Regional Election disputes. The Constitutional Court was given jurisdiction to decide disputes regarding Regional Election results due to this reform. By judgment number 97/PUU-XI/2013, the Constitutional Court revoked this power. In response to this judgment, the President and the House of Representatives of Republic of Indonesia issued Law No.8 of 2015, which stated that the Constitutional Court would redetermine the Regional Election results until a special election court was established. The fundamental issue addressed in this paper is the necessity of converting Bawaslu into a special election court and the form and scope of Bawaslu after it has been changed. A normative legal research technique is used in this work. The study's findings show that Bawaslu actuality as a quasi-judicial entity that works as an investigator and public prosecutor in electoral crime cases supports the argument for its transition into an independent election special court.